PENGARUH KOMPETENSI GURU TERHADAP KINERJA GURU DI SMA NEGERI 7 KABUPATEN TEBO - Pratiwi Indah Sari, Feby Anggraini, (SJEE (Scientific Journals of Economic Education), 2018)
This study aims to determine the description of respondents and the influence of teacher competence on teacher performance in SMA Negeri 7 Kabupaten Tebo. Based on data analysis on the results of research that there is a significant influence between teacher competence on teacher performance in SMA Negeri 7 Kabupaten Tebo. With the result of model summary R = 0,505 and R Square = 0,342. In coefficient, the value of t = 9,258 with α (sig) = 0,006. Because α (Sig) <0,05, regression can be used to predict teacher competence at 95% confidence level. In coefficient the value of B constant = 70,599, states that if the teacher competence variable is ignored, then the teacher's performance = 70,599. Meanwhile, the variable value for teacher competence (X) is 1,210 stating that if the teacher's competency level is included, the teacher's performance increases around 1.210.Keyword : Teacher Competencies, Teacher Performance.